Democracia e voto: uma defesa do direito de abstenção - Silva, Fabio Túlio Correia (2000)
The present work regards democracy and suffrage, in which it is emphatically discussed if the compulsory vote is capable of existing together in harmony with the principles that come from the democratic spirit. The present study is di ided in two parts, reaching a total of seven chapters. The first part (chapters 1 to 4) deals with the concept of the democratic regime. The second part regards the suffrage and the way ít must be seen from a strictl democratic point of view. ln the first two chapters, democracy is chosen as the best regime compared to the others, highlighting values praised by it, such as freedom, equality pluralism and the tolerance toward those who are or think different. Then, differing the expression "suffrage" from "vote" is intended determining their concepts and their juridical nature. After, we face the matter of political alienation. ho e abstention in elections represents one of its features, and finding a solution propo ed b the democratic regime in order to deal with this kind of behavior of the citizen is aimed. ln the sixth chapter, the argument that the compulsory vote gives legitimacy to po er is put to test, having as basis empirical data provided by institutions with credibili . and reliable people. ln the beginning of the final chapter, abstention is defined as well as ho . e eral peoples' legislations deal with this subject, in Europe and in America. Such information is compared to the Brazilian reality, and we also have an overview of the con titutional history. The elector who only votes because he is obliged to is studied with the objecti e of finding out if he has any important characteristic which makes him different from the pontaneou vote r, the one who intends to vote, even if voting were a faculty. The forms and functions of the political representation are discus ed with the objective of finding out if the compulsory vote, at any time, can improve them. In the end of the last chapter, finding out if there is any relationship between the obligation of oting and the predisposition to the preservation of the present political solutions is tried there i if the compulsoriness encourages or not the conservative attitude. We conclude that the compulsory vote does not give any meaningful contribution to the democratic cause.